Modeling Mode Choice Behavior of Motorcyclists in Malaysia - Sheikh Abdul Kadir, Ibrahim (2006)
In Malaysia, motorcycle use has grown in popularity in the past decades and this has resulted in increased casualties among motorcyclists. However, earlier studies focused primarily on motorcycle safety issues rather than identifying factors that influence motorcycle use and motorcyclists’ mode choice behavior. To overcome these problems, this study focused on the concept of exposure control measures such as an alternative to road transport as a countermeasure aimed at shifting motorcycle users to other safer modes in order to reduce the number of motorcycle road accidents. This study developed a model for motorcyclist mode choice behavior and potential mode shift from the motorcycle to other safer modes.